Perceived Constraints and Suggestions of SHGs in Kerala - Sajesh, V.K; Singh, P. (Indian Journal of Extension Education, 2022)
The process of social engineering initiated by the Self Help Groups has generated wider interest in the society and SHGs have been upheld as new paradigm of societal transformation. But, as in the case of any other institution there are many bottlenecks in this movement also. If these constraints are idenitified and removed timely, they will hamper the philosophy of SHGs. The present study was conducted on the groups promoted under Kerala State Poverty Eradication Mission. The study revealed that there are doubts regarding sustainability of groups after withdrawal of promoting institutions SHGs need infrastructural support and assistance for maintaining accounts. There should be effective strategy to deal with the local politics.